2021
DOI: 10.1038/s41388-021-01900-8
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-activated SPRY4-IT1 promotes cancer cell metastasis by downregulating TCEB1 mRNA via Staufen1-mediated mRNA decay

Abstract: Previous study demonstrated that most long non-coding RNAs (lncRNAs) function as competing endogenous RNAs or molecular sponges to negatively modulate miRNA and regulate tumor development. However, the molecular mechanisms of lncRNAs in cancer are not fully understood. Our study describes the role of the lncRNA SPRY4 intronic transcript 1 (SPRY4-IT1) in cancer metastasis by mechanisms related to Staufen1 (STAU1)-mediated mRNA decay (SMD). Briefly, we found that, high SPRY4-IT1 expression was associated with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Multiple transcription factors (TFs) are activated during tumorigenesis and tumor progression. The TFs, such as STAT1, STAT3, ZEB1, NF-kB, have been found to mediate CRC progression via modulating the expression of lncRNAs (40)(41)(42)(43). YY1 is a multifunctional protein that can activate or inhibit gene expression according to changes in conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple transcription factors (TFs) are activated during tumorigenesis and tumor progression. The TFs, such as STAT1, STAT3, ZEB1, NF-kB, have been found to mediate CRC progression via modulating the expression of lncRNAs (40)(41)(42)(43). YY1 is a multifunctional protein that can activate or inhibit gene expression according to changes in conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, EMT can be triggered by SPRY4-IT1 in cervical cancer, colorectal cancer, and hepatocellular carcinomas [190][191][192]. What is more, SPRY4-IT1 is transcriptionally activated by NF-κB and promotes staufen-mediated degradation of transcription elongation factor B subunit 1 (TCEB1) mRNA to upregulate HIF-1α levels [193]. Thus, it is probable that SPRY4-IT1 can control the expression of other ncRNAs, such as circ_ZNF91, which is regulated by HIF-1α (see Section 2.5.3 about circ_ZNF91).…”
Section: Spry4-it1mentioning
confidence: 99%
“…It participates in the transport of transcripts to various subcellular localizations. Expression of SPRY4-IT1 is also activated by NF-κB/p65 ( 5 ).…”
Section: Cell Line Studiesmentioning
confidence: 99%
“…Using a panel of colon, breast, and ovarian cancer tissues, Zhao et al. have found that elevation of SPRY4-IT1 expression is associated with aggressive behavior and poor clinical outcome of patients ( 5 ). Another study has shown that SPRY4-IT1 overexpression in breast cancer tissues is associated with a larger neoplasm bulk and higher pathological stage ( 7 ).…”
Section: Human Studiesmentioning
confidence: 99%